2003
DOI: 10.1007/s00270-002-2628-z
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Central Vein Stenosis and Occlusion Following Upper Extremity PICC and Port Placement

Abstract: The purpose of this study was to determine the incidence of central vein stenosis and occlusion following upper extremity placement of peripherally inserted central venous catheters (PICCs) and venous ports. One hundred fifty-four patients who underwent venography of the ipsilateral central veins prior to initial and subsequent venous access device insertion were retrospectively identified. All follow-up venograms were interpreted at the time of catheter placement by one interventional radiologist over a 5-yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
84
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 154 publications
(87 citation statements)
references
References 16 publications
2
84
0
1
Order By: Relevance
“…8 Unlike the relatively high rate of venous thrombosis from PICCs in the study by Allen et al, lower rates of thrombosis associated with PICC were reported in other studies (2.5% to 7%). 7,[16][17][18] Recently Evans et al conducted a prospective observational study of PICC insertions at an academic medical center with a level I trauma center over a 1-year period and reported that 3.0% of symptomatic patients with PICC lines developed UEDVT, and the most common risk factors were prior DVT and surgery lasting > 1 hour. 18 They emphasized that the size of CVCs was significantly associated with increasing risk of PICC-associated DVT.…”
Section: Risk Factors For Uedvtmentioning
confidence: 99%
“…8 Unlike the relatively high rate of venous thrombosis from PICCs in the study by Allen et al, lower rates of thrombosis associated with PICC were reported in other studies (2.5% to 7%). 7,[16][17][18] Recently Evans et al conducted a prospective observational study of PICC insertions at an academic medical center with a level I trauma center over a 1-year period and reported that 3.0% of symptomatic patients with PICC lines developed UEDVT, and the most common risk factors were prior DVT and surgery lasting > 1 hour. 18 They emphasized that the size of CVCs was significantly associated with increasing risk of PICC-associated DVT.…”
Section: Risk Factors For Uedvtmentioning
confidence: 99%
“…Unfortunately, all the available treatment options have poor longterm patency, requiring repetitive intervention. 6,7,8 and sometimes due to stenosis patient has to undergo special and costly imaging to undergo catherization at atypical sites. 9 Few studies conducted on various type of populations has been conducted and data on the prevalence of central venous stenosis following catheterization in Pakistan.…”
Section: Introductionmentioning
confidence: 99%
“…PICC placement enables blood sampling and continuous vascular access without frequent venipunctures or direct cannulation of central veins, and these conveniences contribute to their expanding popularity (22,23). Because PICC use has increased, potential concerns about bloodstream infections, thromboses, and stenoses of central and peripheral veins have emerged (11)(12)(13)24,25).…”
Section: Discussionmentioning
confidence: 99%
“…Their use shortens the length of stay in hospitals and nursing facilities, and utilization has increased rapidly over the past 15 years (10,11). However, PICC use also is associated with stenosis, thrombosis, and obliteration of the central and peripheral veins in which they dwell (12,13), and these complications may have important long-term consequences for patients who subsequently require HD vascular access. Patients with CKD often have complex preexisting comorbid conditions that may result in PICC exposure, potentially increasing their risk for loss of veins (14).…”
Section: Introductionmentioning
confidence: 99%